Isolation, identification and characterization of lignocellulolytic aerobic and anaerobic fungi in one- and two-phase biogas plants. (November 2018) - Young, Diana; Dollhofer, Veronika; Callaghan, Tony Martin; Reitberger, Stefan; Lebuhn, Michael; Benz, J. Philipp
Highlights: Aerobic and anaerobic fungi were detected in different types of biogas plant. Anaerobic fungi were actively transcribing endo -β-1, 4-glucanase in a fermenter. A Trichoderma capillare isolate showed high lignocellulolytic potential. Abstract: Aerobic and anaerobic fungi are among the most effective plant biomass degraders known and have high potential to increase the efficiency of lignocellulosic biomass utilization, such as for biogas generation. However, limited information is available on their contribution to such industrial processes. Therefore, the presence of fungi along the biogas production chain of one-phase and two-phase biogas plants in Germany was analyzed. Seventeen aerobic species of Zygomycota, Ascomycota and Basidiomycota were identified, including efficient producers of lignocellulases, such as Trichoderma capillare isolated from a hydrolysis tank and Coprinopsis cinerea from fibers separated from pressed digestate. Five anaerobic fungal species of the phylum Neocallimastigomycota (comprising two novel clades) were present in an slightly acidic fermenter of a biogas plant fed with cow manure displaying endoglucanase transcriptional activity. The broad fungal presence demonstrated in this study can serve developing bioaugmentation systems with relevant lignocellulolytic fungi to improve biogas production from recalcitrant fiber material.